Keep going in adversity - using a resilience perspective to understand the narratives of long-term social assistance recipients in Sweden - Marttila Anneli; Johansson Eva; Whitehead Margaret; Burström Bo (BMC, 2013)
Abstract Introduction In Sweden, means-tested social assistance serves as a temporary, last resort safety net. However, increasing numbers of people are receiving it for longer periods and about a third has assistance for more than a year. The aim of this study was to explore the ways social assistance recipients manage long lasting adversity and their roles as active, rather than passive, agents in this process, using a resilience perspective. Method The study is based on thirteen in-depth interviews with long-term social assistance recipients from diverse areas in Stockholm County. The interviews were guided by narrative inquiry to interpret and construct stories of experiences and are part of a larger qualitative study exploring experiences of living on social assistance in Sweden. Results Experiences of cumulative adversity during many years compounded recipients' difficulties in finding ways out of hardship. They had different strategies to deal with adversities, and many had underlying "core problems", including mental health problems, which had not been properly resolved. Recipients' showed resistance in adverse situations. Some made attempts to find ways out of hardship, whereas others struggled mainly to achieve a sense of mastering life. They received important support from individual professionals in different authorities, but mostly the help from the welfare system was fragmented. Conclusions Social assistance recipients in this study demonstrated agency in ways of managing long lasting difficulties, sometimes caused by "core problems", which were often accumulated into complex difficulties. Resilience was about keeping going and resisting these difficulties. To find ways out of social assistance required help from different welfare agencies and professionals and was hindered by the fragmentation of services. This study shows that there is a need for more long-term personalised, comprehensive support, including interventions both to increase individual well-being and self-esteem and to open up opportunities for education and employment. Adequate benefit levels and overall quality of welfare services such as health and social care, day care and schools, are of major importance for those in greatest need.